Canonical penal sanctions for nancial malfeasance - KALETA, PAWEŁ (Prawo Kanoniczne, 2017)
Financial malfeasance, both in the eld of administration and alienation of ecclesiastical goods might contribute to nancial losses, unnecessary scandal of the faithful, as well as the weakening of public trust. In order to prevent such malfeasance, the Church must seek eective methods which will allow to observe the canon law. e aim of this article was to show the penalties for the nancial malfeasance in the canonical legal system. Interestingly that ecclesiastical legislator does not use the concept of „nancial malfeasance”. However, we can nd nine examples of nancial malfeasances in Book VI of the 1983 Code. e following actions can be related to nancial malfeasances: 1) impeding the use of ecclesiastical goods (can.1375), 2) invalid alienation of ecclesiastical goods (can. 1377), 3) simony (can. 1380), 5) illegitimate prot from Mass oerings (can. 1385), 6) bribery (can. 1386), 7) abuse of authority and culpable negligence in performing act of ecclesiastical power or ministry or oce (can. 1389 §1-2), 8) production and use of false documents (can. 1391), 9) clerics carrying out commercial activities (can. 1392). For such oenses, the legislator determines penalties ferendae sententiae which may be imposed on the oender by judicial or administrative process. e legislator does not provide for penalties latae sententiae for nancial malfeasances. For simony and illegitimate prots from Mass oerings leg- islator provides for a penalty of imposing censure. In the case of simony is mandatory sanction (c. 1380), while for the oense of illegitimate prots from Mass oerings is optional one (can. 1385). It can be supposed that the most severe penal sanctions for nancial malfeasance is deprivation of oce that the judge may impose, depend- ing on the severity and harm done. is is an optional penal imposed for abusing of ecclesiastical power or an oce (can. 1389 § 1). In other cases, the ecclesiastical legislator provides for a just penalty ferendae sententiae. If penalties are indeterminate their imposition belongs to the Ordinary or judge. e particular law is to be observed which in place of indeterminate penalty ferendae sententiae it may establish a penalty determined or obli- gated (can. 1315 § 1). In accordance with can. 1317 particular law can not establish a penalty of dismissal from the clerical state.